Corrosion behavior and failure mechanism of electromagnetic pulse welded joints between galvanized steel and aluminum alloy sheets. (April 2021) - Wang, Shaoluo; Luo, Kang; Sun, Tao; Li, Guangyao; Cui, Junjia
Graphical abstract: Highlights: Corrosion behavior of aluminum/galvanized steel and aluminum/ungalvanized steel MPW joints was investigated and compared. Morphologies and corrosion products at the MPW interface were observed and analyzed by SEM and EDS. Corrosion failure mechanisms of the two types of MPW joints were revealed. Abstract: Dissimilar material welded joints will inevitably suffer atmospheric corrosion during service, which may lead to premature failure of the dissimilar welded joints. Hence, in present study, corrosion behavior and mechanism of aluminum/galvanized steel and aluminum/ungalvanized steel magnetic pulse welding (MPW) joints were compared and discussed systematically. Neutral salt spray (NSS) tests, electrochemical tests, and microscopic observations were conducted. Results manifested that mechanical performance of the two MPW joints decreased with increasing ageing time, but the mechanical property decline law was different. Degradation degree of mechanical property of aluminum/non-galvanized steel joints was significantly lower than that of aluminum/galvanized steel joints, and the strength of the former was more than twice that of the latter. Corrosion mechanisms of two MPW joints were revealed by analyzing morphologies and corrosion products of the joints. Aluminum/galvanized steel joints were destroyed due to the corrosion of welded area by NaCl salt spray from arc-shaped weld area. However, galvanic cell was formed in the lap area of aluminum/ungalvanized steel joint, and galvanic corrosion occurred; it mainly caused aluminum sheet to be damaged, thus reducing its mechanical performance. Total electrochemical corrosion resistance of aluminum/galvanized steel MPW joints was stronger than that of aluminum/non-galvanized steel joints. Difference in corrosion property between the two MPW joints was mainly owing to the existence of zinc layer. Presence of zinc layer could descend the total electrochemical corrosion rate of aluminum/steel joints, but it also reduced the strength of the joints. This resulted in different corrosion types, thereby causing different failure modes and fracture mechanisms.